2019
DOI: 10.2139/ssrn.3377010
|View full text |Cite
|
Sign up to set email alerts
|

Russian Business under Economic Sanctions: Is There Regional Heterogeneity?

Abstract: The sanctions against Russia, beginning in early 2014, provide us with a unique opportunity to study whether, and how sanctions affect a vast territorial global superpower. This study attempts to empirically examine the economic impact of this event, paying particular attention to the existence or nonexistence of its regional heterogeneity. For these purposes, this study used a dataset from a survey that asked the executive managers of Russian regional companies to assess the impact on their management activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The article [71] assessed the presence of spatial heterogeneity of the effect of sanctions imposed against Russia in 2014. It was found that companies in the eastern and western regions have equally felt the negative effects of the sanctions.…”
Section: Discussionmentioning
confidence: 99%
“…The article [71] assessed the presence of spatial heterogeneity of the effect of sanctions imposed against Russia in 2014. It was found that companies in the eastern and western regions have equally felt the negative effects of the sanctions.…”
Section: Discussionmentioning
confidence: 99%